(untitled) (Jurnal Bina Praja, 2021)
Asset management in the public sector is important to provide quality public services. One of the important public assets is the regional property that manages by the regional government. Various problems often occurred related to asset management in Indonesia’s public sector, especially the management issue that follows regulations. The research aims to examine the management of public sector assets in The Government of Indonesia, especially regional property, which refers to Indonesia’s prevailing laws and regulations, namely Government Regulation number 27 of 2014. The research was conducted in Indonesia at the Minahasa District government of North Sulawesi Province. The research method used descriptive qualitative, focusing on investigating the use and utilization of regional property and locus at the Regional Financial and Asset Management Agency (BPKAD) in Minahasa Regency. The data collection method in this research is an interview with several key point informants. The informants consist of top-level management, middle management, and staff of BPKAD, with a total of nine informants. The research findings indicate that Regional Property Management by the Minahasa Regional Financial and Asset Management Agency has been carried out under applicable regulations, namely Government Regulation Number 27 of 2014. Several suggestions were given to interested parties. The limitations of this research were limited to specific objects, only general discussion, and only one case study.